Accounts of gender diverse university students who abstain from alcohol use - Ward, Logan; Riggs, D.; Breen, Lauren (2016)
Gender diverse and transgender people report elevated alcohol use compared with the general population yet no studies have examined motives to abstain or limit alcohol consumption within this vulnerable population. A thematic analysis of interviews with seven gender diverse people identified two overarching themes: Awareness of the safety implications of alcohol and Access to non-drinking spaces. Participants acknowledged that drinking alcohol was a social norm yet were hesitant to drink, especially in public places, due to safety concerns and highlighted a need for non-drinking, LGBTI-friendly spaces. These findings have implications for promoting non-drinking strategies of benefit to gender diverse communities.